Identification of BST2 Contributing to the Development of Glioblastoma Based on Bioinformatics Analysis - Kong, Yang; Xue, Zhiwei; Wang, Haiying; Cui, Guangqiang; Chen, Anjing; Liu, Jie; Wang, Jian; Li, Xingang; Huang, Bin (Frontiers in Genetics, 2022)
Rigorous molecular analysis of the immune cell environment and immune response of human tumors has led to immune checkpoint inhibitors as one of the most promising strategies for the treatment of human cancer. However, in human glioblastoma multiforme (GBM) which develops in part by attracting immune cell types intrinsic to the human brain (microglia), standard immunotherapy has yielded inconsistent results in experimental models and patients. Here, we analyzed publicly available expression datasets to identify molecules possibly associated with immune response originating from or influencing the tumor microenvironment in primary tumor samples. Using three glioma datasets (GSE16011, Rembrandt-glioma and TCGA-glioma), we first analyzed the data to distinguish between GBMs of high and low tumor cell purity, a reflection of the cellular composition of the tumor microenvironment, and second, to identify differentially expressed genes (DEGs) between these two groups using GSEA and other analyses. Tumor purity was negatively correlated with patient prognosis. The interferon gamma-related gene BST2 emerged as a DEG that was highly expressed in GBM and negatively correlated with tumor purity. BST2high tumors also tended to harbor PTEN mutations (31 vs. 9%, BST2high versus BST2low) while BST2low tumors more often had sustained TP53 mutations (8 versus 36%, BST2high versus BST2low). Prognosis of patients with BST2high tumors was also poor relative to patients with BST2low tumors. Further molecular in silico analysis demonstrated that high expression of BST2 was negatively correlated with CD8+ T cells but positively correlated with macrophages with an M2 phenotype. Further functional analysis demonstrated that BST2 was associated with multiple immune checkpoints and cytokines, and may promote tumorigenesis and progression through interferon gamma, IL6/JAK/STAT3 signaling, IL2/STAT5 signaling and the TNF-α signaling via NF-kB pathway. Finally, a series of experiments confirmed that the expression of BST2 can be significantly increased by IFN induction, and knockdown of BST2 can significantly inhibit the growth and invasion of GBM cells, and may affect the phenotype of tumor-associated macrophages. In conclusion, BST2 may promote the progression of GBM and may be a target for treatment.